Ekoteologi sebagai Solusi Ekologis - Nuryamujiatun; Ghani, Dadang (Islamuna: Jurnal Studi Keislaman, 2025)
The ecological crisis is a global problem that increasingly threatens the sustainability of human life and nature. Environmental damage, climate change, and excessive exploitation of natural resources indicate an imbalance in the relationship between humans and nature. This article aims to examine ecotheology as an ecological solution to address the environmental crisis through a theological and ethical approach. This research uses qualitative methods with a library study approach to various scientific and religious literature relevant to ecotheology and environmental issues. The results show that ecotheology positions nature as God's creation with intrinsic value and must be preserved as a form of human moral and spiritual responsibility. Ecotheology encourages a paradigm shift from an anthropocentric perspective to a more harmonious relationship between God, humans, and nature. By integrating the values ​​of faith, ethics, and concrete action, ecotheology has the potential to become a moral foundation for building ecological awareness and realizing a sustainable life.